Use of an implantable loop recorder to increase the diagnostic yield in unexplained syncope: results from the PICTURE registry - Edvardsson, Nils (Oxford University Press, 2011)
AIMS: To collect information on the use of the Reveal implantable loop recorder (ILR) in the patient care pathway and to investigate its effectiveness in the diagnosis of unexplained recurrent syncope in everyday clinical practice. METHODS AND RESULTS: Prospective, multicentre, observational study conducted in 2006–2009 in 10 European countries and Israel. Eligible patients had recurrent unexplained syncope or pre-syncope. Subjects received a Reveal Plus, DX or XT. Follow up was until the first recurrence of a syncopal event leading to a diagnosis or for ≥1 year. In the course of the study, patients were evaluated by an average of three different specialists for management of their syncope and underwent a median of 13 tests (range 9–20). Significant physical trauma had been experienced in association with a syncopal episode by 36% of patients. Average follow-up time after ILR implant was 10 ± 6 months. Follow-up visit data were available for 570 subjects. The percentages of patients with recurrence of syncope were 19, 26, and 36% after 3, 6, and 12 months, respectively. Of 218 events within the study, ILR-guided diagnosis was obtained in 170 cases (78%), of which 128 (75%) were cardiac. CONCLUSION: A large number of diagnostic tests were undertaken in patients with unexplained syncope without providing conclusive data. In contrast, the ILR revealed or contributed to establishing the mechanism of syncope in the vast majority of patients. The findings support the recommendation in current guidelines that an ILR should be implanted early rather than late in the evaluation of unexplained syncope.